Conscious and unconscious performance monitoring: Evidence from patients with schizophrenia - Charles, Lucie; Gaillard, Raphaël; Amado, Isabelle; Krebs, Marie-Odile; Bendjemaa, Narjes; Dehaene, Stanislas (NeuroImage (Orlando, Fla.), 2017)
The ability to detect our own errors is an essential component of action monitoring. Using a masking paradigm in normal adults, we recently discovered that some error-detection processes can proceed without awareness, while other markers of performance monitoring such as the Error-Related Negativity (ERN) are tightly linked to conscious perception. Interestingly, research on cognitive deficit in schizophrenia has shown that the ERN is altered in these patients. In the present study, we therefore tested if the error detection impairment in schizophrenia is specific to conscious perception or is also found under non-conscious conditions, probing whether these performance monitoring processes are truly distinct. Thirteen patients with schizophrenia and thirteen age-matched healthy control subjects performed a speeded number comparison task on masked stimuli while EEG and MEG signals were recorded. Conscious perception and error-detection were assessed on a trial-by-trial basis using subjective reports of visibility and confidence. We found that patients with schizophrenia presented altered cingulate error-detection responses in conscious trials, as reflected by a decreased ERN. By contrast, on unconscious trials, both controls and schizophrenia patients performed above chance in evaluating the likelihood of having made an error. This dissociation confirms the existence of two distinct performance monitoring systems, and suggests that conscious metacognition in schizophrenia is specifically altered while non-conscious performance monitoring remains preserved.